Continuing Education as a Dominant Element of the Modern Educational Paradigm - Volkovetska, Romana; Mudrokha, Valentyna; Demchuk, Nataliia (Pedagogical Discourse, 2020)
The article deals with the issue of developing the system aiming at continuing education as a dominant element of modern education doctrine. The need for large-scale studies of the phenomenon and the formation of a separate special paradigm at both theoretical and practical levels, taking account of the «multi-professionalism» as a characteristic feature of the labour market, the processes of vocational globalization, the priority of information technology, the introduction of outcome-based approach as of the high priority, critically short period of the half-life for modern competences has been substantiated. Based on the analysis of disparate elements from the experience of the continuing education formation and implementation, the main problematic issues the solution of which will ensure the formation of a holistic paradigm of continuing education have been synthesized, in particular: 1) terminology standardization for the continuing education; 2) establishment of the general state of educational strategy at the level of principles, tasks, structure, forms and methods, etc.; 3) ensuring proper regulatory and legal support for the functioning of continuing education as a holistic system at the level of laws and regulations; 4) formation of the optimal hierarchy of educational institutions, which will create and provide educational products and educational services in the framework of the continuing education by means of the infrastructure of field-oriented institutions and organizations; 5) use of modern information technologies of e-learning.